An active magnetic bearing for thin-walled rotors: vibrational dynamics and stabilizing control - Matthew Cole (2018)
IEEE This paper describes a novel active magnetic bearing with distributed actuation, designed for contact-free support of a thin-walled rotor. A full dynamic analysis, control formulation and experimental evaluation are presented. Important aspects of the bearing operation include vibration excitation of the rotor wall due to asymmetries in manufacture and assembly, and the limits of stable operation with respect to static loading of the bearing. For the proposed design, the vibratory dynamics for flexure of the rotor wall are accounted for explicitly in the actuator coil-winding and driving scheme so that coupling of the levitation control with the wall dynamics is minimized. This enables the selection of control feedback laws based on rigid-body dynamic considerations alone. Dynamic performance is investigated by theoretical and experimental study involving a prototype rotor-bearing system. The operating principles are validated and the dynamic behavior shown to align well with the theoretical predictions.